The Ribosomal Protein L28 Gene Induces Sorafenib Resistance in Hepatocellular Carcinoma - Shi, Yi; Wang, Xiaojiang; Zhu, Qiong; Chen, Gang (Frontiers in Oncology, 2021)
Sorafenib is the first molecular-targeted drug for the treatment of advanced hepatocellular carcinoma (HCC). However, its treatment efficiency decreases after a short period of time because of the development of drug resistance. This study investigates the role of key genes in regulating sorafenib-resistance and elucidates the mechanism of drug resistance in hepatocellular carcinoma. The HCC HepG2 cells were used to generate a sorafenib-resistant cell model by culturing the cells in gradually increasing concentration of sorafenib. RNA microarray was applied to profile gene expression and screen key genes associated with sorafenib resistance. Specific targets were knockdown in sorafenib-resistant HepG2 cells for functional studies. The HCC model was established in ACI rats using Morris hepatoma3924A cells to validate selected genes associated with sorafenib resistance in vivo. The HepG2 sorafenib-resistant cell model was successfully established. The IC50 of sorafenib was 9.988M in HepG2 sorafenib-resistant cells. A total of 35 up-regulated genes were detected by expression profile chip. High-content screening technology was used and a potential drug-resistance related gene RPL28 was filtered out. After knocking down RPL28 in HepG2 sorafenib-resistant cells, the results of cell proliferation and apoptosis illustrated that RPL28 is the key gene involving in drug resistance. Furthermore, it was found that both RNA and protein expression of RPL28 increased in HepG2 sorafenib-resistant specimens of Morris Hepatoma rats. In addition, the expression of proliferative protein Ki-67 increased in sorafenib-resistant cells. Collectively, our study suggested that RPL28 is a key gene inducing sorafenib resistance in HCC and could be a potential target for the treatment of drug-resistant HCC.